1987
DOI: 10.1159/000298777
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Balloon Catheter for Ultrasound Evaluation of Pelvic Masses

Abstract: Pelvic masses can be diagnosed by pelvic ultrasonography. Difficulties may be encountered to identify the organ origin of a pelvic mass. An intrauterine marker is proposed to facilitate the diagnosis by the exact localization of the uterus and its relationship to other pelvic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…2 Such masses have been routinely diagnosed using hysteroscopy, which has a detection rate of less than 70%, confirmed by histologic evaluation. 3 Saline infusion sonohysterography is another method for diagnosing intrauterine lesions. 3,4 Its main contribution for diagnosing residual trophoblastic tissue is its specificity, which has been reported to be as high as 100%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Such masses have been routinely diagnosed using hysteroscopy, which has a detection rate of less than 70%, confirmed by histologic evaluation. 3 Saline infusion sonohysterography is another method for diagnosing intrauterine lesions. 3,4 Its main contribution for diagnosing residual trophoblastic tissue is its specificity, which has been reported to be as high as 100%.…”
mentioning
confidence: 99%
“…3 Saline infusion sonohysterography is another method for diagnosing intrauterine lesions. 3,4 Its main contribution for diagnosing residual trophoblastic tissue is its specificity, which has been reported to be as high as 100%. 5 Color Doppler sonographic evaluation of a suspected intrauterine echogenic mass may also help to identify the type of the mass.…”
mentioning
confidence: 99%
“…2 Sonohysterography, i.e., ultrasonography with intrauterine saline instillation, is another method for the diagnosis of intrauterine lesions. 3,4 This technique may improve our ability to evaluate intrauterine disease. The aim of this study was to examine the accuracy, efficacy, and safety of sonohysterography in diagnosing residual trophoblastic tissue.…”
mentioning
confidence: 99%
“…Furthermore, Achiron et al (5) showed that the addition of Doppler studies to TVS does not dramatically improve our ability to diagnose RPOC. Even hysteroscopy was shown to have a detection rate of less than 70%, as confirmed by histologic examination (6).…”
mentioning
confidence: 94%
“…Two-dimensional ultrasound was believed to be a promising tool for the detection of RPOC, but several studies have shown that its sensitivity is insufficiently high (2)(3)(4)(5). Although it would seem that hysteroscopy should be the ideal tool for diagnosing RPOC, it was shown to have a detection rate of less than 70%, as confirmed by histologic examination (6), thus hysteroscopy cannot accurately differentiate between RPOC and blood clots. We (7,8), and others (9) have shown that sonohysterography is an excellent tool for the diagnosis of RPOC.…”
mentioning
confidence: 99%